Paradise, WV - Rufus, Rob (Nashville : Turner Publishing, 2021)
"The teenage children of a convicted serial killer try to prove his innocence when a true-crime podcast reinvigorates interest in the case. Their fate intersects with cults, killers, cops, and convicts on the backroads of West Virginia in one brutal, unforgettable crash"--.